Composite Lymphoma with Follicular Lymphoma Transformation to Clonally Related Epstein–Barr Virus (EBV) Positive Diffuse Large B-Cell Lymphoma and EBV-PositiveClassic Hodgkin Lymphoma - Ryder, Christopher B.; Saeed, Hayder; Hussaini, Mohammad (Case Reports in Hematology, 2023)
While the Epstein–Barr virus (EBV) is known to drive de novo lymphomagenesis, it may rarely contribute to transformation of indolent lymphoma as well. Some EBV-related lymphomas represent a diagnostic challenge with important prognostic and therapeutic implications. We describe a case of follicular lymphoma (FL) transformation to both EBV + diffuse large B-cell lymphoma (DLBCL) and EBV + classic Hodgkin lymphoma (cHL), the latter of which was only identified retrospectively after selective outgrowth during DLBCL therapy. Finally, we describe successful salvage therapy with brentuximab vedotin plus nivolumab. This is the first known case of composite lymphoma with FL, EBV + DLBCL, and EBV + cHL within a single lymph node. The disease course highlights the importance of careful morphologic examination and comprehensive immunophenotypic characterization of EBV + lymphomas to ensure proper clinical care and underscores the potential for novel therapies currently under investigation. This trial is registered with NCT01671813.